Peran Taman Pendidikan Qur’an dalam pengembangan karakter Religious - Natania, Friska Oliva (Maliki Interdisciplinary Journal, 2024)
Character education is the most important aspect that must be taught to children from an early age. Character is an individual habit in terms of thinking that influences behavior and actions in everyday life. Meanwhile, religious character is a behavior or action that obeys the teachings that are appropriate and related to God Almighty. The importance of religious character education can be instilled in children from an early age through the Taman Pendidikan Qur’an (TPQ), which can be expected to help children understand the contents of the verses of the Koran as a guide for Muslims. Formation of religious character through aspects of knowledge, feelings and actions. In developing religious character, habituation through teaching is needed such as obedience to teachers, tolerance among friends, love for God’s majesty and humility. Basically, TPQ aims to create a child who is virtuous and has good morals and spiritual abilities in accordance with Islamic teachings. To create it requires an understanding of akhlaqul karimah. In addition, TPQ is also a place for delivering da’wah related to Islamic education through teaching in theory and practice that can be implemented in everyday life. TPQ is also a place to study religious knowledge in individuals which influences patterns of thinking, behavior and acting according to good and true Islamic teachings. Keywords: Character Education, Character Development, Religious Character, Role of Character Education, Taman Pendidikan Karakter (TPQ)Character education is the most important aspect that must be taught to children from an early age. Character is an individual habit in terms of thinking that influences behavior and actions in everyday life. Meanwhile, religious character is a behavior or action that obeys the teachings that are appropriate and related to God Almighty. The importance of religious character education can be instilled in children from an early age through the Taman Pendidikan Qur’an (TPQ), which can be expected to help children understand the contents of the verses of the Koran as a guide for Muslims. Formation of religious character through aspects of knowledge, feelings and actions. In developing religious character, habituation through teaching is needed such as obedience to teachers, tolerance among friends, love for God’s majesty and humility. Basically, TPQ aims to create a child who is virtuous and has good morals and spiritual abilities in accordance with Islamic teachings. To create it requires an understanding of akhlaqul karimah. In addition, TPQ is also a place for delivering da’wah related to Islamic education through teaching in theory and practice that can be implemented in everyday life. TPQ is also a place to study religious knowledge in individuals which influences patterns of thinking, behavior and acting according to good and true Islamic teachings.